Measures of Interjoint Coordination Post-stroke Across Different Upper Limb Movement Tasks - Schwarz, Anne; Veerbeek, Janne M.; Held, Jeremia P. O.; Buurke, Jaap H.; Luft, Andreas R. (Frontiers in Bioengineering and Biotechnology, 2021)
Background-Deficits in interjoint coordination, such as the consolidation of pathological flexor synergies, are frequent symptoms in stroke subjects with upper limb impairments that hinder them from regaining normal motor function. Kinematic measurements allow fine-grained assessment of movement pathologies, thereby complementing clinical scales, like the Fugl-Meyer Motor Assessment of the Upper Extremity (FMMA-UE). The study goal was to investigate the effects of the performed task, the tested arm, the dominant affected hand, upper limb function, and age on kinematics of the elbow, shoulder, and trunk. The construct validity of the metrics was examined by relating them with each other, the FMMA-UE, and its arm-section. Methods-A cross-sectional observational study including chronic stroke patients with mild-to-moderate upper limb motor impairment. Kinematic measurements were taken using a wearable sensor suit while performing four movements with both upper limbs: (1) isolated shoulder flexion, (2) pointing, (3) reach-to-grasp a glass, and (4) key insertion. The kinematic parameters included the joint ranges of shoulder abduction/adduction, shoulder flexion/extension, and elbow flexion/extension; trunk displacement; shoulder-elbow correlation coefficient; median slope; and curve efficiency. Effects of the task and tested arm on the metrics were investigated using a mixed model analysis. The validity of metrics compared to clinically measured interjoint coordination (FMMA-UE) were done by correlation analysis. Results-Twenty-six subjects were included in the analysis. The movement task and tested arm showed significant effects (p<0.05) on all kinematic parameters. Hand dominance resulted in significant effects on shoulder flexion/extension and curve efficiency. The level of upper limb function showed influences on curve efficiency and the factor age on median slope. Relations with the FMMA-UE revealed the strongest and significant correlation for curve efficiency (r = 0.75), followed by shoulder flexion/extension (r = 0.68), elbow flexion/extension (r = 0.53) and shoulder abduction/adduction (r = 0.49). Curve efficiency additionally correlated significantly with the arm subsection focusing on synergistic control (r = 0.59). Conclusion-Kinematic parameters of the upper limb after stroke were influenced largely by the task. These results underpin the necessity to assess different relevant functional movements close to real world conditions rather than relying solely on the FMMA-UE. Clinicaltrials.gov Identifier NCT03135093 and BASEC-ID 2016-02075.